PENERAPAN PENDEKATAN VISUALIZATION AUDITORY KINESTETIC UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMP - Amalia Fitrianti Nurmuslimah; Rani Stefani; Siti Chotimah (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2019)
The purpose of this research is to improve the ability of mathematical understanding of junior high school students on three-dimensional objects with circular bases by using Visualization Auditory Kinestetic (VAK) approach. This research uses descriptive qualitative method with the subject of research is the students of class IX Junior high school in West Bandung. The results of this study indicate an increase in student learning outcomes in understanding three-dimensional objects with circular bases.